2021
DOI: 10.1021/acs.orglett.1c03129
|View full text |Cite
|
Sign up to set email alerts
|

Selective Thiocyanation and Aromatic Amination To Achieve Organized Annulation of Enaminone with Thiocyanate

Abstract: A tandem insertion of thiocyanate to enamine was performed for the regioselective synthesis of multisubstituted benzoimidazo­[2,1-b]­thiazoles. This method was shown to be effective in addressing the issue of isomerization encountered in common strategies. With a change made to the leading group on the aniline fragment of enamine, the reaction achieved different transformations, thus enabling multisubstituted benzo­[4,5]­imidazo­[2,1-b]­thiazoles and thiazoles in satisfactory yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In 2021, our group found that using a metal catalyst, with the promotion of iodine under O 2 , we could obtain thiazolimide derivatives as by-products in modest yields. 37 Pharmaceutical researchers have showed great interest in green approaches for the development of medicinal products. 38 In recent decades continuous attempts have been made to incorporate green strategies in the synthesis of thiazole and its derivatives (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, our group found that using a metal catalyst, with the promotion of iodine under O 2 , we could obtain thiazolimide derivatives as by-products in modest yields. 37 Pharmaceutical researchers have showed great interest in green approaches for the development of medicinal products. 38 In recent decades continuous attempts have been made to incorporate green strategies in the synthesis of thiazole and its derivatives (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, our group found that using a metal catalyst, with the promotion of iodine under O 2 , we could obtain thiazolimide derivatives as by-products in modest yields. 37…”
Section: Introductionmentioning
confidence: 99%
“…The construction of functional fused heterocycles and the combination of thiocyanation with other elementary reactions to generate multirings has been the focus of our research for many years . Thiocyanate, which is commercially available, serves as an odorless, atom-economic, and multifunctional source of sulfur, nitrogen, and bridge carbon.…”
mentioning
confidence: 99%
“…Thiocyanates are widely used as intermediates in synthetic chemistry. For instance, thiocyanates easily transform into thiols, disulfides, trifluoromethyl thioethers, carbamodithioates, and various heterocycles . Thiocyanate-containing natural products have been reported to be involved in the mechanism of DNA damage. , Thus, thiocyanates are attracting the broad interest of many chemists and biologists.…”
mentioning
confidence: 99%